1975
DOI: 10.1007/bf02532761
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxygenase isozymes of peanut

Abstract: Lipoxygenase was isolated and partially purified from peanut seed by ammonium sulfate precipitation, gel filtration, and ion exchange column chromatography. Three isozymes of lipoxygenase were identified. Two had pH optima of 6.2, and the other an optimum of 8.3. Molecular weight of each isozyme was 7.3 x 10(4), as determined by gel filtration. The alkaline optimum isozyme was not inhibited by NaCN and was inhibited by CaCl2 except at very low concentrations. The acid optimum isozymes were inhibited by NaCN an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 13 publications
4
26
0
Order By: Relevance
“…These results are similar to that reported for French bean lipoxygenase (Kermasha and Metche, 1986). Cyanide ion was reported to inhibit partially purified lipoxygenase from peanut a t concentrations greater than 1 mM (Siddiqi and Tappel, 1957), while Sanders et al (1975) reported that cyanide ion concentration below 14 mM had little effect on the activity of a purified alkaline isozyme of peanut lipoxygenase but inhibited an acid isozyme lipoxygenase from the same seed. De Lumen et al (1978) demonstrated that 50% inhibition of green bean lipoxygenase was obtained a t 20 mM final cyanide concentration.…”
Section: Resultssupporting
confidence: 90%
“…These results are similar to that reported for French bean lipoxygenase (Kermasha and Metche, 1986). Cyanide ion was reported to inhibit partially purified lipoxygenase from peanut a t concentrations greater than 1 mM (Siddiqi and Tappel, 1957), while Sanders et al (1975) reported that cyanide ion concentration below 14 mM had little effect on the activity of a purified alkaline isozyme of peanut lipoxygenase but inhibited an acid isozyme lipoxygenase from the same seed. De Lumen et al (1978) demonstrated that 50% inhibition of green bean lipoxygenase was obtained a t 20 mM final cyanide concentration.…”
Section: Resultssupporting
confidence: 90%
“…In the production of fatty acid hydroperoxides, the addition of an oxygen molecule to a polyunsaturated fatty acid is catalyzed by lipoxygenase enzymes. In peanuts, lipoxygenases are reported to be involved in the response to Aspergillus colonization (Burow et al., ; Sanders, Pattee, & Singleton, ). Lineoleic acid is one of the main fatty acids present in peanut lipids.…”
Section: Resultsmentioning
confidence: 99%
“…Heme was identified as having the second highest fold change and was significantly different between the market types ( P < 0.05). Peanut peroxidase, a heme peroxidase, is a classical extracellular plant peroxidase (Sanders et al., ). Extracellular plant peroxidases have been implicated in cell wall metabolism as well as in wound defense and plant hormone metabolism (Burow et al., ; Schuller, Ban, van Huystee, McPherson, & Poulos, ).…”
Section: Resultsmentioning
confidence: 99%
“…Samples were kept cold throughout the extraction process except when centrifuged. Enzymatic activity of the extract was measured polarigraphically in a reaction vessel fitted with a Clark oxygen electrode (Sanders et al, 1975). Lipoxygenase activity was determined by adding 200 μΕ of the aqueous enzyme extract to 1.5 mL of 82.50 linoleic acid and 0.8% Tween 20 in pH 6.4, 0.1 Μ phosphate buffer and aerated 0.2 mL phosphate buffer in a 1.7-μΕ reaction vessel.…”
Section: Methodsmentioning
confidence: 99%